Dosificación óptima de hidróxido de sodio como reactante de la alcalinidad del jabón en barra a base de piñón (Jatropha Curcas L.) - Saldarriaga Zambrano, Gregorio Eulices (2014)
The goal of this research was to determine the optimal dosage of hydroxide sodium to obtain the ideal alkalinity of soap bar for washing, using pinion as raw material. To carry on this study, a completely random design with three replicates was executed; the factor study was the percentage of hydroxide sodium in pinion paste (9%, 11.5% and 14%), a witness control was used a hand-crafted soap with 16% hydroxide sodium solution. Bromatological characteristics (alkalinity free, pH, matter insoluble in water, insoluble in alcohol and foaming material level) were evaluated to each of the three treatments and control, for this, 12 experimental units of 250 g each were used. Analysis were made using the methods stablished by the current INEN soaps standards. The results showed that treatment T1 with 9% solution of hydroxide sodium, had the lowest and best value of alkalinity free and pH being 0.08% and 10.23 respectively. On the other hand the result for insoluble matter was 4.69%, insoluble matter in alcohol 6.71% and 29,19 cm3 of foaming level. Thus it is concluded that the 9% of hydroxide sodium solution is suitable for preparing soap of pinion.